Application of Sliding Mode Control in Indirect Field Oriented Control (IFOC) for Model Based Controller - Aaditya, Angga Wahyu; Happyanto, Dedid Cahya; Sumantri, Bambang (EMITTER International Journal of Engineering Technology, 2017)
Indirect Field Oriented Control (IFOC) is one of the vector control methods that can be applied to induction motor in the industrial world rather than Direct Field Oriented Control (DFOC) because of the flux is obtained from the formulation. However, IFOC can not guarantee the robustness and stability of the systems. Stability analysis such as Lyapunov Stability Theory can be used to make the system stable but not the robustness. Model based controller that can guarantee the stability and robustness such as sliding mode control (SMC) and fuzzy needs to be added in IFOC system to achieve proportional response system. Robust current regulator using sliding mode control was designed in this paper from state space model for model based controller. In transient response and under disturbance SMC shows better performance than PID in rising time and robustness at rotor speed and stator current.